2009
DOI: 10.1186/1471-2180-9-268
|View full text |Cite
|
Sign up to set email alerts
|

Virulence potential of five major pathogenicity islands (SPI-1 to SPI-5) of Salmonella enterica serovar Enteritidis for chickens

Abstract: BackgroundSalmonella is a highly successful parasite of reptiles, birds and mammals. Its ability to infect and colonise such a broad range of hosts coincided with the introduction of new genetic determinants, among them 5 major pathogenicity islands (SPI1-5), into the Salmonella genome. However, only limited information is available on how each of these pathogenicity islands influences the ability of Salmonella to infect chickens. In this study, we therefore constructed Salmonella Enteritidis mutants with each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 26 publications
7
93
0
4
Order By: Relevance
“…Their study indicates the importance of both SPI-1 and SPI-2 in colonization of the liver and spleen, but also shows that although at much lower levels than the wild-type, mutants lacking one or both of SPI-1 and SPI-2 can still be isolated from the liver and spleen, further confirming our results. They found no difference in caecal colonization by any of their strains, in accordance with our results (Rychlik et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Their study indicates the importance of both SPI-1 and SPI-2 in colonization of the liver and spleen, but also shows that although at much lower levels than the wild-type, mutants lacking one or both of SPI-1 and SPI-2 can still be isolated from the liver and spleen, further confirming our results. They found no difference in caecal colonization by any of their strains, in accordance with our results (Rychlik et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…However, very recent work by Rychlik and co-workers, published after completion of our animal trials, describes the complete knockout of all the SPI regions (together and separately), and their effect on colonization of 1-day-old chicks (Rychlik et al, 2009). Also, at least partial deletions of SPI-2 have been produced in S. Typhimurium, as well as full deletions of SPI-1 ( Colonization of the liver and spleen of challenged birds was often quite low; therefore, portions of the liver and spleen were enriched in selenite broth to increase detection sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also revealed that genes encoded by SPI-1 TTSS are involved in intestinal invasion whereas genes encoded on SPI-2 are required for systemic infection and survival within macrophages (Desin et al, 2009;Dieye et al, 2009;Jones et al, 2007;Li et al, 2009;Rychlík et al, 2009;Wisner et al, 2010). Mutations in the genes encoding secretory effector proteins or genes that regulate their expression lead to virulence attenuation in S. Enteritidis (Amy et al, 2004;Fardini et al, 2007;Parker & GuardPetter, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella flagella activate Toll-like receptor (TLR)-5 on enterocyte surfaces (Iqbal et al, 2005;Subramanian and Qadri, 2006) triggering a cascade of cellular events, which lead to the secretion of cytokines and chemokines responsible for stimulating innate and adaptive immunity, mainly through activation of dendritic and T cells (McSorley et al, 2002;Iqbal et al, 2005;Salazar-Gonzalez and McSorley, 2005).…”
Section: Introductionmentioning
confidence: 99%